PENGUATAN PEMBELAJARAN AQIDAH AKHLAK DALAM MEMBENTUK ETIKA MENGHORMATI GURU PADA SISWA MADRASAH IBTIDAIYAH - Annisaul Maghfiroh; Ahmad Arifin (JECE (Journal of Ethics and Character Education), 2025)
This study aims to analyze the strengthening of Aqidah Akhlak learning in shaping students’ ethics of respecting teachers at the Madrasah Ibtidaiyah level. The background of this research is based on the importance of instilling noble moral values from an early age as a foundation for students’ character development. Aqidah Akhlak learning, which is derived from the Qur’an and Hadith, plays a strategic role in fostering respectful, polite, and ethical attitudes toward teachers as educators and moral role models. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of the school principal, Aqidah Akhlak teachers, and parents. Data were collected through in-depth interviews, observation, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that strengthening Aqidah Akhlak learning through teachers’ role modeling, habituation practices, and a religious school culture effectively shapes students’ ethics in respecting teachers. However, the consistency of these ethical behaviors requires continuous support from the family environment. This study concludes that synergy between schools and parents is essential to optimize the formation of students’ ethics in respecting teachers at the Madrasah Ibtidaiyah level.